2019
DOI: 10.3390/antiox8020036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the In Vitro Wound-Healing Activity of Calabrian Honeys

Abstract: The healing of skin wounds and particularly chronic wounds, such as diabetic foot ulcers, is still a clinical emergency. Despite the many therapeutic tools that are available so far, none seems to be really effective and safe. In this context, we highlighted the renewed wound healing activity of honey, a viscous aromatic and sweet food, by way of in vitro wound-healing assays, using the HaCaT cell line. Specifically, we investigated five monofloral or multifloral honeys from different Calabrian provinces using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 42 publications
0
38
0
1
Order By: Relevance
“…The maintenance of intestinal permeability as a feature for overcoming the development of severe diseases, including inflammatory bowel disease and food allergies, is a growing topic in the field of nutrition science. Various substances have been used over the years, [3][4][5] including the conventional steroid drugs, able to improve gut health through the reduction of inflammatory mediators [6]. Polyphenols, which are the most important secondary metabolites of plants, demonstrated to modulate the expression and/or production of numerous proteins, but also to regulate the intestinal ecosystem [7].…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of intestinal permeability as a feature for overcoming the development of severe diseases, including inflammatory bowel disease and food allergies, is a growing topic in the field of nutrition science. Various substances have been used over the years, [3][4][5] including the conventional steroid drugs, able to improve gut health through the reduction of inflammatory mediators [6]. Polyphenols, which are the most important secondary metabolites of plants, demonstrated to modulate the expression and/or production of numerous proteins, but also to regulate the intestinal ecosystem [7].…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the dose-effect relationship of TMM was biphasic, showing a bell-shaped effect. Natural products have been frequently shown to have a biphasic pharmacological effect, both in vitro and in vivo [ 38 , 39 , 40 ]. In particular, we previously reported that a standardized Hypericum perforatum L. extract, which is a well-known anti-depressant herbal drug, can exert an anti-nociceptive effect in mice models of neuropathic pain at lower doses compared to the one used for treating depression, with a mechanism of action involving the opioid system.…”
Section: Discussionmentioning
confidence: 99%
“…Pinocembrin resulted as the principal component of the total extract, recoverable from methanol fraction after column chromatography. Literature data report that pinocembrin is a flavonoid endowed with antioxidant [21] and anti-inflammatory properties, exerted by downregulating tumor necrosis factor alpha (TNF-α), interleukin 1 beta (IL-1β), and interleukin 6 (IL-6). These activities are also achieved by significantly suppressing the phosphorylation and activation of extracellular signal-regulated kinase (ERK), c-Jun NH2-terminal kinase (JNK) and p38MAPK, as well as by reducing the phosphorylation of IkBα, directly involved in nuclear factor kappa B (NF-kB) regulation, as demonstrated by in vitro and in vivo studies [22].…”
Section: Introductionmentioning
confidence: 99%